Menumbuhkan Kemandirian Beribadah Anak melalui Pendampingan Praktek Wudhu dan Sholat di Madrasah Ibtidaiyah - Muhammad Noor Habil; Muhammad Syabrina (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to foster children’s independence in worship through mentoring on the practice of ablution (wudhu) and prayer (sholat) at Madrasah Ibtidaiyah Al-Jihad. The activity was motivated by preliminary observations showing that most first and second-grade students already recognized the basic procedures of wudhu and sholat but still needed guidance in mastering the correct order of movements and recitations. Therefore, this mentoring program was carried out as an effort to develop students’ religious character from an early age through direct practice and habituation in the school environment. The implementation method used a participatory and educative approach consisting of several stages, including initial observation, collaborative planning with teachers, mentoring in wudhu and sholat practices, and final evaluation. The activity was carried out collaboratively among students, teachers, and university mentors, creating an active, interactive, and joyful learning atmosphere. The results showed a significant improvement in students’ independence and understanding in performing wudhu and sholat correctly. Students were able to memorize the sequence of wudhu, perform prayer movements more accurately, and worship with greater focus and discipline without constant supervision. Teachers also reported increased student awareness and consistency in performing daily prayers after the mentoring sessions. Overall, this program had a positive impact on fostering the habit of worship in the school environment and demonstrated that hands-on practice combined with exemplary guidance is an effective approach to instill religious values and build independent character in young learners